The exploitation of ultra-low-enthalpy geothermal energy in an ORC process in combination with RES and a heat pump - Novosel, Urška (JET on-line, 2015)
The paper presents a model of a binary-cycle hybrid power plant to be located in Topolšica, Šalek Valley, Slovenia. It is based on an ORC process and utilises several different renewable energy sources: geothermal energy, solar energy, and wood biomass energy. The portion of geothermal energy is so low that it is used in the system as a source of energy for a heat pump, thus increasing the inlet temperature of the ORC process. The model of the hybrid ORC power plant dealt with in this paper is intended only for electricity production. The energy source used first is geothermal water from a well, entering the heat pump to heat the heat pump working medium. Solar energy and wood biomass energy are sources of heat flow, additionally heating the ORC process working medium. The paper presents thermodynamic and economic analyses of this potential system.
Keywords: economic analysis; energy analysis; geotermalna energija; kombinirane elektrarne; lesna biomasa; obnovljivi energetski viri; ORC proces; ORC process; renewable energy resources; sončna energija